The Impact of Institutional Factors on the Use of Blended Learning by Faculty Members - F. Bahrami; M. Nazarzadeh Zare (Fanāvarī-i āmūzish, 2023)
Background and Objectives: Institutions usually bring the technologies they need from their surrounding environments into the organization. Therefore, a university as one of the important social institutions, under the influence of the electronic revolution and the emergence of new technologies in its surrounding environment, has moved towards the use of multimedia systems and electronic education; however, the use of electronic education, despite countless opportunities, has also brought major problems and challenges, some of which have been mentioned in previous studies, including the lack of face-to-face communication and interaction between the educator and the learner. Hence, the solution offered in e-learning to face this problem is the blended learning approach. Studies have shown that various factors such as educational, environmental, institutional, and organizational factors are effective in applying blended learning, and not paying attention to any of them can cause the failure of this type of teaching and learning. Therefore, the aim of the present study was to investigate the impact of institutional factors on the use of blended learning by the faculty members of Malayer University.Methods: The present study was applied research in terms of purpose, cross-sectional in terms of time, and in terms of method of collecting the required data, it adopted a descriptive-correlation design using structural equation modeling. The statistical population of the present study included all the faculty members of Malayer University with the number of 153 people. Due to the limited size of the research community, all faculty members were tested, and finally, 140 faculty members participated in the study with a return rate of 92%. The tools of data collection were questionnaires of institutional factors and blended learning. For data analysis, descriptive statistics (frequency, percentage, mean) and inferential (correlation test and path analysis) methods were used in SPSS version 22 and Smart PLS version 6 statistical software.Findings: The findings obtained from the statistical analysis of the data indicated a positive and significant impact of the normative factor with a path coefficient (0.151) on the use of blended learning by the faculty members, and the mimetic factor with a path coefficient (0.413) on the use of blended learning by faculty members, and the coercive factor with a path coefficient (0.362) had an impact on the use of blended learning by faculty members. Also, the measurement and fit indices of the model indicated its appropriateness.Conclusion: Overall, the study showed that institutional factors (normative factors, coercive factors, and mimetic factors) have a great impact on the use of blended learning by faculty members. Hence, considering the following suggestions can help to institutionalize the use of blended learning in the academic context, namely the establishment of regulations and internal laws regarding the use of blended learning in the teaching-learning process at universities, more culturalization in the use of blended learning in the teaching-learning process by faculty members, imitating successful universities and institutions in the field of implementing blended learning, training faculty members on how to apply blended learning in teaching, encouraging more faculty members to use blended learning, and finally considering more educational privileges for the use of blended learning in teaching by faculty members.